Compromise and Care of the Brain's Compartments: The Quintessence of the Neurovascular Unit - Maiese, Kenneth (Current Neurovascular Research, 2006)
During the 17th century, the human body began to be viewed as a system of subunits and independent compartments. This eventually led to the first human anatomical descriptions that mapped the body into different organs and tissues. As a result of this